Hypersynchrony in sarcomeric hypertrophic cardiomyopathy: description and mechanistic approach using multimodal electro-mechanical non-invasive cartography (HSYNC study) - Réant, Patricia; Bonnet, Guillaume; Dubé, Frédérique; Massie, Charles; Reynaud, Amélie; Michaud, Matthieu; Duchateau, Josselin; Lafitte, Stéphane (Frontiers in Cardiovascular Medicine, 2024)
Background Little is known about left ventricular (LV) sequences of contraction and electrical activation in hypertrophic cardiomyopathy (HCM). A better understanding of the underlying relation between mechanical and electrical activation may allow the identification of predictive response criteria to right ventricular DDD pacing in obstructive patients. Objective To describe LV mechanical and electrical activation sequences in HCM patients compared to controls. Materials and methods We prospectively studied, in 40 HCM patients (20 obstructive and 20 non-obstructive) and 20 healthy controls: (1) mechanical activation using echocardiography at rest and cardiac magnetic resonance imaging, (2) electrical activation using 3-dimensional electrocardiographic mapping (ECM). Results In echocardiography, healthy controls had a physiological apex-to-base delay (ABD) during contraction (23.8 ± 16.2 ms). Among the 40 HCM patients, 18 HCM patients presented a loss of this ABD (<10 ms, defining hypersynchrony) more frequently than controls (45% vs. 5%, p = 0.017). These patients had a lower LV end-diastolic volume (71.4 ± 9.7 ml/m2 vs. 82.4 ± 14.8 ml/m2, p = 0.01), lower native T1 values (988 ± 32 ms vs. 1,028 ± 39 ms, p = 0.001) and tended to have lower LV mass (80.7 ± 23.7 g/m2 vs. 94.5 ± 25.3 g/m2, p = 0.08) compared with HCM patients that had a physiological contraction sequence. There was no significant relation between ABD and LV outflow tract obstruction. While HCM patients with a physiological contraction sequence presented an ECM close to those encountered in controls, patients with a loss of ABD presented a particular pattern of ECM with the first potential more frequently occurring in the postero-basal region. Conclusion The LV contraction sequence can be modified in HCM patients, with a loss of the physiological ABD, and is associated with smaller LV dimensions and a particular pattern of ECM. Further research is needed to determine whether this pattern is related to an electrical substrate or is the consequence of the hypertrophied heart's specific geometry. Clinical trial registration ClinicalTrial.gov: NCT02559726.